DAMPAK PENGALIHAN FUNGSI LAHAN PERTANIAN INDONESIA - Nabila, Maura; Anandaputri, Karina Aurelia (Universitas Negeri Yogyakarta, 2023)
The agricultural sector is being discussed about the problem of land use change because the country is improving the country's economy by developing the industrial sector so that the impact of these actions can affect the welfare of farmers and the community, reduced food production, if the country lacks food, the country will import food, this will be detrimental to the country because the country will have to import food. If the country lacks food then the country will import food, this will harm the country because as it is known that Indonesia is very dependent on food, and if the country does not have enough food because of the diversion of agricultural land then the country will supply food from other countries so that food is very dependent on other countries. other countries so that food is very dependent on imports and this will increase the nominal state expenditure in food production. Will increase the nominal state expenditure in the state budget. This research using a literature study approach. Data was obtained from news sources and several journals that examine the conversion of agricultural land functions. This research uses dependency theory in analyzing the data. The results of this study show that the agricultural sector is declining due to land conversion to improve infrastructure, industry, settlements.